Peranan Zikir dan Doa Terhadap Kesehatan Jiwa di Tarekat Naqsyabandiyah Al-Kholidiyah di Desa Sei Pasir Kecamatan Sei Kepayang Timur Kabupaten Asahan - Rizki Gunawan Lubis (UIN Sumatera Utara, 2021)
This article will explore the role of remembrance and prayer on mental health in the Naqsyabandiyah Order in Sei Pasir Village, Asahan Regency. The Naqsabandiyah Order is not just a ritual teaching, it focuses on the human spiritual approach to God Almighty. The implementation of remembrance is part of the method of approaching Allah SWT. The formulation of the problem in this study is 1. The role of remembrance and prayer for mental health in the Naqsyabandiyah Order located in Sei Pasir Village, Sei Kepayang Timur District, Asahan Regency 2) How are the practices of the Naqsabandiyah Order in the Naqsyabandiyah Order located in Sei Pasir Village, Subdistrict Sei Kepayang Timur, Asahan Regency 3) How is the influence of the teachings of the Naqsabandiyah Order in Sei Pasir Village, Sei Kepayang Timur District, Asahan Regency on the surrounding community? This study aims to determine the form of the role of remembrance and prayer on mental health in the Naqsyabandiyah Al Kholidiyah Order in Sei Pasir Village, Sei Kepayang Timur District, Asahan Regency. This type of research is a qualitative field research. This research is pursued by the steps of collecting, classifying and analyzing or processing data, making conclusions and reports with the main aim of making an overview of a situation objectively from a description. The approach according to the researcher according to the theme of this research is the sociocultural approach. Zikir in the Naqsyabandiyah Order in Sei Pasir Village, Sei Kepayang Timur District, Asahan Regency, from remembrance of ismu substance, remembrance of lathaif and with practices such as repentance, talqin allegiance, and remembrance. The results of the study illustrate that people who follow the teachings of Tariqah Naqsabandiyah in their lives are calmer, more open to the way, the problems they face are felt with a well-controlled mind. The daily life of the tariqah congregation is more confident in the destiny of life from Allah SWT, more istiqomah in living life, in society the congregation has more high social awareness, and upholds the dignity of fellow living creatures as Allah's creation. in Sei Pasir Village, Sei Kepayang Timur District, Asahan Regency, more giving social roles in social life to people who follow tariqah. Because he can be trusted in carrying out his mandate as a leader and prioritizes the public interest.